Exogenous Melatonin Promotes the Salt Tolerance by Removing Active Oxygen and Maintaining Ion Balance in Wheat (Triticum aestivum L.) - Zhang, Zhihui; Liu, Liantao; Li, Hongye; Zhang, Shaocong; Fu, Xiaoyi; Zhai, Xiuzhen; Yang, Na; Shen, Jiaming; Li, Ruiqi; Li, Dongxiao (Frontiers in Plant Science, 2022)
Melatonin (MT) is a small molecule indole hormone that plays an important role in biological and abiotic stress resistance. Although previous studies have confirmed that MT promotes the normal development of plants under stress by mediating physiological regulation mechanism. However, the physiological mechanism of exogenous MT regulating seed germination and seedling growth of wheat under salt stress is still unclear. In this study, NaCl stress decreased germination rate and inhibited seedling growth of wheat, but shoot length, root length and plant weight of SM15 did not change significantly. Addition of 300 µM MT in the cultivation solution directly promoted germination rate of SM15 and ZM18, promoted lateral roots production, but decreased germination rate of JM22 and inhibited the length of germ and radicle of three varieties under salt stress. For wheat seedling, MT application could increase proline content, soluble protein, soluble sugar, Ca2+ content, and vital amino acid content in leaf to keep high water status and low level of H2O2 content and [K+]/[Na+] ratio; meantime, MT increased root vigor, [K+]/[Na+] ratio and decreased H2O2 content in root induced by salt stress. In conclusion, MT enhances salt tolerance in wheat seeds and seedlings by regulating synthesis of soluble protein and sugar; ion compartmentation at root and leaf of plant; the enhancement of enzymatic systems; and changes in amino acid levels. Salt-resistance is different with varieties and conditions. SM15 was a higher salt-resistant variety, JM22 was salt-sensitive. In wheat production, the optimal concentration, varieties, and MT application method should be considered comprehensively at the sowing and seedling stages.